Election politics and the New Partnership for Africa's Development (NEPAD) : comparing the 2001 elections in Zambia and Uganda - Oloka-Onyango, J. (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2004.